Training In The Production Of Additional Food Based On Local Food As A Stunting Prevention Effort In Kuro Village, Karangbinangun - Asyaul Wasiah; Berlina Martha Algama; Fatmasari Fatmasari (Healthy-Mu Journal, 2024)
The nutritional status of mothers and children is an important factor that must be of great concern to health workers . Indonesia is one of the countries that has a fairly high stunting rate, the age of toddlers is a very important period in the process of child growth and development physically and intelligently. One way that can be done is to increase awareness of good nutrition by providing supplementary food (PMT). The purpose of this community service program is to provide education about Supplementary Feeding. Food ingredients used in PMT should be ingredients that are available or can be produced locally, so that the possibility of program sustainability is greater. The method used in the community service program carried out in Kuro Karangbinangun Village is counseling and demonstration on how to make PMT. The results of this activity are the distribution of additional food and a demonstration of how to make PMT which aims to improve nutrition for mothers and toddlers as well as adding information about how to make additional food innovations that contain high nutrition such as innovative fish nuggets and green bean pudding